Clause structure of Northern Havyaka Kannaḍa (Dravidian) : a tagmemic analysis - Ullrich, Helen E. (Publication (Dravidian Linguistics Association) ;, 1980)
Linguistic study of the Havyaka dialect of the Kannada language.